Prevalence and Predictors of Anxiety and Depressive Symptoms Among International Medical Students in China During COVID-19 Pandemic - Yuan, Lu-Lu; Lu, Lu; Wang, Xue-Hang; Guo, Xiao-Xi; Ren, Hong; Gao, Yu-Qin; Pan, Bo-Chen (Frontiers in Psychiatry, 2021)
Background The rapid spread of Coronavirus Disease-19(COVID-19) infection has been the most important public health crisis across the globe since the end of 2019. Anxiety and depression are the most common mental health problems among people during the pandemic, and many studies have reported anxiety and depressive symptoms in college students. However, information on the mental health status of international medical students during this critical period of time has been scarce, which hinders the efforts in making proper policy or strategies to help these students. The present study aims to explore the prevalence of anxiety and depressive symptoms in international medical students in China and to find out the factors that have potential predictive value for anxiety and depressive symptoms. Method A cross-sectional study was carried out for international medical students during November 2020 at China Medical University in Shenyang, China.519 international students were interviewed with questionnaires containing demographic variables, Stressors in school, Generalized Anxiety Disorder Assessment(GAD-7), Patient Health Questionnaire-9(PHQ-9), Simplified Coping Style Questionnaire(SCSQ), Perceived Stress Scale(PSS-10), the Multidimensional Scale of Perceived Social Support(MSPSS), Revised Life Orientation Test(LOT-R) and Resilience Scale-14(RS-14). Univariate logistic regression and logistic regression analyses were conducted to explore the predictive factors of anxiety symptoms and depressive symptoms. Results The prevalence of anxiety symptoms and depressive symptoms in the sample population was 28.5%(148/519) and 31.6%(164/519), respectively. Stressors in school(β=0.176,OR=1.192,CI:1.102-1.289), negative coping style(β=0.639,OR=1.894,CI:1.287–2.788) and perceived stress(β=0.230,OR=1.258,CI:1.184-1.337) were found to be the predictors of anxiety symptoms among the international medical students; while gender(β=-0.594,OR=0.552,CI:0.315-0.968), stay up late(β=0.828,OR=2.288,CI: 1.182-4.431), current place of residence(β=1.082,OR=2.951,CI:1.256-6.931), stressors in the school(β=0.303,OR=1.354,CI:1.266-1.496), negative coping style(β=0.866,OR=2.377,CI:1.516-3.725), perceived stress(β=0.233,OR=1.262,CI:1.180-1.351) were found to be predictors of depressive symptoms. Conclusion The prevalence of anxiety symptoms and depressive symptoms was moderate among international medical students in China. The communal predictors of anxiety and depressive symptoms were stressors in school, negative coping style and perceived stress; while demographic factors such as gender(male), stay up late at night and current place of residence were found associated with depressive symptoms. These results suggest that proper stress management and specific interventions are needed to help students maintain their mental health during the COVID-19 pandemic period.